1987
DOI: 10.1111/j.1464-5491.1987.tb00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Foot Pressure in Early Diabetic Neuropathy

Abstract: Dynamic foot pressure has been studied in 44 diabetic subjects of mean age 52 years with no clinical evidence of neuropathy and in an age and sex matched non-diabetic control group. Vibration perception threshold (VPT), sensory (SCV), and motor conduction velocities (MCV) were also measured in the diabetic subjects. Sixteen diabetic subjects (Group A) had abnormally high pressures under the metatarsal heads (greater than 10 kg/cm2), whereas the remaining 28 diabetic subjects had normal results (Group B). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
1
9

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 9 publications
1
65
1
9
Order By: Relevance
“…After our initial confirmation that plantar ulcers invariably occurred at sites of high pressure [35], we demonstrated that foot pressure abnormalities occur early in the natural history of neuropathy [51]. In a longitudinal study it was confirmed that sites of peak pressure change over time, an observation with important implications for orthotists [52].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 75%
“…After our initial confirmation that plantar ulcers invariably occurred at sites of high pressure [35], we demonstrated that foot pressure abnormalities occur early in the natural history of neuropathy [51]. In a longitudinal study it was confirmed that sites of peak pressure change over time, an observation with important implications for orthotists [52].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 75%
“…In industrialized countries, diabetes mellitus with insensitive feet is the main reason for foot pressure ulcers that could ultimately lead to lower limb amputations (5,6). Amputees wearing prosthesis need to accommodate high ambulatory loadings during their daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…Worse, the rates of diabetes-related amputation are increasing 1 . Diabetes-associated neuropathy, peripheral vascular disease, and infection all contribute to the process that produces ulceration and diabetic foot disease 12,[14][15][16][17][18][19][20] . Altered mechanical forces, especially high plantar pressures, are also an important factor [15][16][17][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…Diabetes-associated neuropathy, peripheral vascular disease, and infection all contribute to the process that produces ulceration and diabetic foot disease 12,[14][15][16][17][18][19][20] . Altered mechanical forces, especially high plantar pressures, are also an important factor [15][16][17][21][22][23][24][25] . Although a specific ulcer-producing pressure threshold has not been identified and appears to vary according to patient-related characteristics, reduction of high plantar pressure in feet that have lost protective sensation is the cornerstone of current prevention and treatment 15,17,19,20,22,26,27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation